2017
DOI: 10.1186/s13075-016-1207-7
|View full text |Cite
|
Sign up to set email alerts
|

The 23-valent pneumococcal polysaccharide vaccine in patients with rheumatoid arthritis: a double-blinded, randomized, placebo-controlled trial

Abstract: BackgroundPneumococcal pneumonia is the most frequent form of pneumonia. We herein assessed the effectiveness of the 23-valent pneumococcal polysaccharide vaccine (PPSV23) in the prevention of pneumonia overall in rheumatoid arthritis (RA) patients at risk for infections. We hypothesized that PPSV23 vaccination is superior in preventing pneumococcal pneumonia compared with placebo in RA patients.MethodsA prospective, multicenter, double-blinded, randomized, placebo-controlled (1:1) trial was conducted across d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 31 publications
0
12
0
6
Order By: Relevance
“…Two pneumococcal vaccines are now available: the 23-valent pneumococcal polysaccharide vaccine (PPSV23) and the 13-valent pneumococcal conjugate vaccine (PCV13). Regarding efficacy, a randomised double-blind trial on the clinical efficacy of PPSV23 in preventing pneumonia in RA patients did not demonstrate an increased efficacy of the vaccine over placebo 123. On the other hand, a retrospective study on the long-term effect of PPSV23 in RA patients treated with MTX showed a relative risk of 9.7 to develop pneumonia in non-vaccinated patients 124.…”
Section: Resultsmentioning
confidence: 97%
“…Two pneumococcal vaccines are now available: the 23-valent pneumococcal polysaccharide vaccine (PPSV23) and the 13-valent pneumococcal conjugate vaccine (PCV13). Regarding efficacy, a randomised double-blind trial on the clinical efficacy of PPSV23 in preventing pneumonia in RA patients did not demonstrate an increased efficacy of the vaccine over placebo 123. On the other hand, a retrospective study on the long-term effect of PPSV23 in RA patients treated with MTX showed a relative risk of 9.7 to develop pneumonia in non-vaccinated patients 124.…”
Section: Resultsmentioning
confidence: 97%
“…Regarding efficacy of pneumococcal vaccination in AIIRD, a randomised double-blind trial on the clinical efficacy of PPSV23 in preventing pneumonia in patients with RA did not demonstrate an increased efficacy of the vaccine over placebo, emphasising the need for a more efficacious vaccine 120. In contrast, a retrospective study on the long-term effect of PPSV23 in 180 patients with RA treated with MTX showed a relative risk of 9.7 to develop pneumonia among non-vaccinated patients 121.…”
Section: Resultsmentioning
confidence: 98%
“…From the previous recommendations and up to August 2018, 34 studies53 76 81 83 84 105–133 and two meta-analyses45 77 have been published on the efficacy, immunogenicity and safety of PPSV23 and the conjugated vaccines PCV7 and PCV13, including evaluation of a combined strategy (tables 7 and 8). 106 128 133…”
Section: Resultsmentioning
confidence: 99%
“…Given the high risk of infection in patients receiving biologic therapy, the 2015 ACR and APLAR guidelines recommended assessment of vaccination history and completion of outstanding vaccination when possible, before initiating bDMARDs. Several RCTs studied the safety and efficacy of pneumococcus, influenza, and HBV vaccination in patients receiving biologic therapy [133][134][135][136][137][138][139][140]. Biologic therapy seems to be unrelated to the side effect of the killed vaccine.…”
Section: Monitoring Strategies Before or During Use Of Bm-dards In Pamentioning
confidence: 99%